Hauntology or the Return of the Real Man: Edging the Žižek-Laclau controversy on populism. - De Vos, Jan (International Journal of Žižek Studies, 2010)
The article offers information on the academic knowledge which addresses the ideology of the real human being in relation to populism. It states on the arguments by Ernesto Laclau on the movement beyond academia, signifying the death of ideology theory and negativity. It mentions on the pseudo-concreteness by Slavoj Žižek which pertains on the role of psychology and late-capitalism in the creation of post-modern society illusion. It relates on Laclau's inexistent and distorted society elaborated by his mysticism theory. It also discusses the depiction of populism in the real men ideology which is argued by Žižek through his hauntology or return of repressed men and Laclau with his class struggle denouncement and identification of people as hegemony fighter.